Adipose tissue oxylipin profile changes with subclinical ketosis and depot in postpartum dairy cows - Bridger B. Sparks; Hunter Ford; Tainara C. Michelotti; Clarissa Strieder-Barboza (Journal of Dairy Science, 2025)
ABSTRACT: Lipolysis of adipose tissue is a natural occurrence during the periparturient period in dairy cows. However, when lipolysis rates exceed the capacity of other tissues to used nonesterified fatty acids, it may lead to the development of ketosis and other diseases. Additionally, PUFA can become oxidized into oxylipins, which modulate inflammation and metabolism. The objective of this work was to identify depot-specific differences on adipose tissue oxylipin profile in dairy cows with and without subclinical ketosis and assess the effects of oxylipins on adipocyte function in vitro. Subcutaneous adipose tissue from the flank (SAT) and visceral adipose tissue from the omentum (VAT) were collected through laparotomy from multiparous dairy cows (5–14 DIM) and grouped according to blood BHB into nonketotic (NK; n = 5; BHB ≤ 0.8 mmol/L) and subclinical ketotic (SCK; n = 5; BHB 1.4 and ≤ 2.6 mmol/L). A targeted lipidome capable of detecting a 154 oxylipins was performed in paired SAT and VAT samples from all animals. Data were analyzed using the PROC GLIMMIX procedure in SAS (v9.4, SAS Institute Inc., Cary, NC) for the effect of depot (SAT, VAT), ketosis status (SCK, NK), and their interaction (depot × ketosis status) on oxylipin abundance. The oxylipins thromboxane-B2 (TXB2), prostaglandin-A2 (PGA2), and 5-hydroxeicostretanoic acid (5-HETE) were selected from lipidomic data based on effects of ketosis status and depot-specificity to further investigate their effects on SAT and VAT adipocyte function. Lipidomic data revealed 50 oxylipins across both adipose tissue depots. SCK was associated with a decreased abundance of TXB2 and tended to associate with an increase in PGA2 and prostaglandin-E1 (PGE1). Additionally, PGE1, 15-keto-prostaglandin-E2, 13,14-dihydro-15-keto-prostaglandin-E2, 5-HETE, and 15-HETE were increased in SAT. Although VAT had a greater abundance of 9,10-dihydroxy-12Z-octadecenoic acid, 12,13-dihydroxy-9Z-octadecenoic acid, 9-oxo-10E,12Z,15Z-octadecatrienoic acid, and 13S-hydroxy-9Z,11E,15Z-octadecatrienoic acid (13[s]-HOTrE). In vitro, an average (AVG) dose of 5-HETE on VAT cells tended to increase proliferation at d 7 compared with the control, HGH dose of TXB2 tended to decrease lipid accumulation in SAT compared with control, and AVG dose of PGA2 on VAT cells tended to lower ROS compared with the control. Overall, postpartum dairy cows have depot-specific adipose tissue lipidomic profiles which are associated with changes in ketosis status.